2020
DOI: 10.1021/acs.jced.0c00084
|View full text |Cite
|
Sign up to set email alerts
|

Isobaric Vapor–Liquid Equilibria for Binary Mixtures of Biomass-Derived γ-Valerolactone + Tetrahydrofuran and 2-Methyltetrahydrofuran

Abstract: 2-Methyltetrahydrofuran (2-MeTHF) can be utilized as a renewable fuel additive, a component of P-fuel, and an alternative solvent for synthesis and catalysis. Tetrahydrofuran (THF) has also been proposed as a blend component and a surfactant additive. Since γ-valerolactone (GVL), which has been identified as a promising renewable platform molecule, can be converted to 2-MeTHF, it could be considered as biomass originated feedstock for its production. In this sense, the corresponding vapor–liquid equilibrium da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 57 publications
0
11
0
Order By: Relevance
“…A 0 = 2.847077, A 1 = −1.324751 × 10 −3 , A 2 = 1.060314 × 10 −6 , T 0 = 478.00 K, and p 0 = 99795 Pa. 18 yp…”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…A 0 = 2.847077, A 1 = −1.324751 × 10 −3 , A 2 = 1.060314 × 10 −6 , T 0 = 478.00 K, and p 0 = 99795 Pa. 18 yp…”
Section: Resultsmentioning
confidence: 98%
“…Equation was used to obtain the activity coefficients (γ i ). The vapor pressure data of GVL were calculated by the Cox-equation (eq ) with the parameters determined by Růžička and coworkers as follows: A 0 = 2.847077, A 1 = −1.324751 × 10 –3 , A 2 = 1.060314 × 10 –6 , T 0 = 478.00 K, and p 0 = 99795 Pa …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The regression resulted in the Antoine constants as follows: A = 5.8942 ± 0.0604, B = 1210.9794 ± 34.0884, and C = −185.0325 ± 3.8818 with a Δ p % value of 0.23 and a root-mean-square deviation (RMSD, eq ) of 0.12. The Antoine constants of 2-MeTHF were calculated in our previous study where p 0 is the vapor pressure, N is the number of measured points, m is the number of estimated parameters, p i ,meas 0 is the measured vapor pressure, p i ,calc 0 is the calculated vapor pressure, and RMSD is the root-mean-square deviation corrected by the number of estimated parameters.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, to design efficient distillation unit(s) for the separation, the determination of binary interaction parameters (BIPs) of 1,4-PDO and 2-MeTHF is highly desired. For some binary mixtures containing 2-MeTHF, there are available VLE data such as its mixture with aliphatic and aromatic hydrocarbons, ethanol, and GVL . It was observed that 2-MeTHF forms azeotrope with ethanol; therefore, the experimental investigation into its mixture with other alcohols, like diols, is highly important.…”
Section: Introductionmentioning
confidence: 99%